2022
DOI: 10.1186/s40662-022-00310-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and prediction of the clinical result with a specific model of mini-scleral contact lens in corneas with keratoconus

Abstract: Background To investigate which factors are correlated with the visual improvement achieved with a specific model of scleral contact lens (SCL) in keratoconus (KC) eyes and to define a model to predict such improvement according to the pre-fitting data. In addition, the changes occurred with the fitting of a specific model of SCL during a period of 3 months in corneas with KC have been investigated. Methods Longitudinal retrospective study includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…3 Along with the improvement in visual acuity, an appreciable improvement in corneal aberrations was also noted in our study. The results were consistent with those shown by Sidi Mohamed Hamida et al 19 and Montalt et al 20 Kumar et al studied the effect of MSL on visual acuity and ocular higher-order aberrations in 15 eyes with keratoconus and concluded that MSL significantly reduced ocular aberrations and improved visual acuity in patients with keratoconus. The sign of vertical coma changed in keratoconus.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…3 Along with the improvement in visual acuity, an appreciable improvement in corneal aberrations was also noted in our study. The results were consistent with those shown by Sidi Mohamed Hamida et al 19 and Montalt et al 20 Kumar et al studied the effect of MSL on visual acuity and ocular higher-order aberrations in 15 eyes with keratoconus and concluded that MSL significantly reduced ocular aberrations and improved visual acuity in patients with keratoconus. The sign of vertical coma changed in keratoconus.…”
Section: Discussionsupporting
confidence: 89%
“…The improvement in aberrations does not guarantee no residual aberrations because contact lens and tear film can only minimize and compensate for anterior surface aberrations but not the posterior surface and internal aberrations. Sidi Mohmed Hamida et al 19 found a significant correlation between the decrease in comatic aberration and the improvement in visual acuity.…”
Section: Discussionmentioning
confidence: 98%
“…However, several factors are correlated with the visual improvement achieved with contact lenses in keratoconus eyes and a predicting model according to the pre-fitting data should be investigated. 55 , 56 …”
Section: Resultsmentioning
confidence: 99%
“…This was an expected result confirming more recent reports focused on keratoconus. 31,32 The CDVA, either with glasses or RCLs, correlated with the selected BOZR and OD in keratoconus but not in the post-CXL cases. It is not abundantly clear why this difference occurred.…”
Section: Discussionmentioning
confidence: 97%